Comparing time-based and event-based prospective memory over short delays. Issue 7 (9th August 2018) - Conte, Angela M.; McBride, Dawn M.
ABSTRACT: The current study compared monitoring in time- and event-based prospective memory (PM). Time- and event-based non-focal task instructions were given after a baseline block of a lexical decision ongoing task. Delay between instruction and presentation of PM cue/time was manipulated between-subjects to examine monitoring across short delays (1–6 min). Longer delays decreased performance in the event-based task, but not in the time-based task. This accuracy decline was accompanied by a decline in monitoring (as measured by PM cost to the ongoing task in the trials immediately before the PM cue was presented) between the 1 and 3 min delays. Monitoring was only evident for the time-based task at the 6 min delay as measured by PM cost to the ongoing task. Clock checks were also not affected by delay, but did increase in frequency as the response time neared. These results suggest that delay from the time of intention formation decreases both accuracy and monitoring in event-based tasks, but does not decrease accuracy or monitoring in time-based tasks.